The catholic teaching protecting truth and life - Lopez Trujillo, Alfonso (Medicina e Morale, 1993)
In the light of the Catholic teaching the Author explains why the Church has chosen and has persistently protected human life: it's God's gift, and man cannot abusively make himself its arbitrator, judge or owner. With alI the threats and attempts on life, especially new life, man should always remember that he has been created by God "in his image and likeness", and that he has a basic and natural vocation for love, which wants to be fullfilled. In fact, when man loses sight of this truth and thinks he can live autonomously, and once he knows his vital dynamics, he wants to command them, at the beginning of life (and at the end of it), with reproductive technologies and contraception.